2009
DOI: 10.1016/j.psyneuen.2009.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin enhances the experience of attachment security

Abstract: Summary Repeated interactions between infant and caregiver result in either secure or insecure relationship attachment patterns, and insecure attachment may affect individual emotion-regulation and health. Given that oxytocin enhances social approach behavior in animals and humans, we hypothesized that oxytocin might also promote the experience of attachment security in humans. Within a 3-week interval 26 healthy male students classified with an insecure attachment pattern were invited twice to an experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
141
1
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(163 citation statements)
references
References 24 publications
10
141
1
5
Order By: Relevance
“…While previous studies on the single-dose effects of OT often report no change in mood state (Baumgartner et al, 2008;Buchheim et al, 2009;Kosfeld et al, 2005;Rimmele et al, 2009), the current results indicate that after two weeks of treatment, feelings of tension and (tentatively) anger were significantly reduced in the OT group, not in the PL group. At least for reports on the IPPA of peer attachment, it appears that inter-individual differences in (baseline) attachment style may play a pivotal role in determining treatment response.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…While previous studies on the single-dose effects of OT often report no change in mood state (Baumgartner et al, 2008;Buchheim et al, 2009;Kosfeld et al, 2005;Rimmele et al, 2009), the current results indicate that after two weeks of treatment, feelings of tension and (tentatively) anger were significantly reduced in the OT group, not in the PL group. At least for reports on the IPPA of peer attachment, it appears that inter-individual differences in (baseline) attachment style may play a pivotal role in determining treatment response.…”
Section: Discussioncontrasting
confidence: 91%
“…Particularly, using a social trust game with monetary stakes, Kosfeld et al (2005) showed that a single-dose of OT significantly increased the readiness to bear social risks arising through interpersonal interactions. Later, Buchheim et al (2009) showed that OT can increase the experience of attachment security, while De Dreu (2012) proved that intranasal OT can facilitate the development of trust and cooperation in particular in adults with high attachment avoidance (by reducing betrayal aversion). Also self-reports on agency towards self or others were shown to be influenced by single doses of OT administration, indicating that in avoidantly attached individuals, OT positively influenced communal traits and agency towards others (Bartz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Attachment style may be particularly relevant in PTSD: insecure attachment, has been associated with higher PTSD symptom severity in trauma-exposed individuals (see Woodhouse et al, 2015 a meta-analysis). Notably, perception of attachment security was improved after OT administration in healthy male students (Buchheim et al, 2009). However, opposite effects of OT administration on attachment have also been found: anxiously attached healthy males remembered their mother as less caring after OT administration, compared with placebo (Bartz et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Importantly, another study from our laboratory demonstrated that intranasal OT (24 IU) specifically improves recognition memory for faces, but not for nonsocial stimuli, which suggests an immediate and selective effect of the peptide strengthening neuronal systems of social memory [134]. Notably, in an initial double-blind, placebo-controlled within-subject design on the effects of OT on attachment, we were recently able to show that a single intranasal administration of 24 IU OT increases the subjective experience of attachment security (assessed with an adult attachment projective picture test) in male students classified with an insecure attachment pattern [20]. As secure attachment is associated with lower stress reactivity and a better ability to socially interact [40], and mediates the implications of early trauma, namely on psychopathology [128], the neuroendocrine mechanisms of attachment may have direct clinical implications for several mental and developmental disorders (see clinical perspectives).…”
Section: Social Cognition and Social Approachmentioning
confidence: 91%